Best bilinear approximations of the classes SΩp,θB of periodic functions of many variables - Solich, Kateryna; Соліч, Катерина (Інститут математики НАН України, 2011)
We obtain exact-order estimates for the best bilinear approximations of the classes SΩ p,θ of periodic functions of many variables in the space Lq under certain restrictions on the parameters p, q, and θ.
Найкращi бiлiнiйнi наближення класiв s Ω p,θb перiодичних функцiй багатьох змiнних
Keywords: best bilinear approximations; the classes $ $ B_ {{p,\theta}}^{\varOmega} $